Research on the Use of Herbal Products in the Treatment of Varroa Infestation - Dragos Moraru; Adrian Rășinar; Roxana Nicoleta Lazăr; Denis Cimpoca; Silvia Pătruică (Scientific Papers Animal Science and Biotechnologies, 2023)
Varroa destructor is a parasite that affects all stages of development of the bee colony, and currently represents one of the greatest dangers in the loss of colonies worldwide. Currently, different types of treatments have been researched and administered, both synthetic products and based on natural substances. As a result, in this study, we made a comparison between the effectiveness of two natural treatments. As a result, in this study we made a comparison between the effectiveness of two natural treatments (Thymo Varo San and Herba Strip) compared to the same number of synthetic treatments (Varachet Forte and Scabatox), all of which are used by beekeepers to control bee infestation with the mite Varroa destructor. The experiment was carried out in August 2021 in Caransebeș, Romania, on a number of 40 bee colonies, distributed in batches of 10 colonies for each treatment used. The results were evaluated at an interval of 1 day, respectively 7 days after administration, and the best results were recorded in the case of the treatment with Thymo Varo San.